Strategi Pengembangan Subsektor Peternakan dalam Rangka Memperkuat Sektor Pertanian di Kabupaten Boyolali - Nuning Setyowati (Sains Peternakan: Jurnal Penelitian Ilmu Peternakan, 2011)
This study aims to identify the position of the livestock subsector within the framework of the agricultural sector development in the Boyolali District. Furthermore, this research also aims to formulate livestock sector development strategy as an effort to improve its performance. This study is a descriptive analytic with analysis tool used is the Typology Klassen and SWOT analysis. The results showed that the livestock subsector is a potential sub-sectors which means that this sub-sector contribution is greater than the GDP contribution Boyolali district but it has a slow growth rate. Livestock sector development strategy in Boyolali district as follow: Increased production of farm commodities and processed products, strengthening of agroindustry based commodity / farm products, strengthening of capital for farmers and agroindustry, marketing business development for farm commodities and processed products, increase the role of cooperatives and GKSI for support of livestock sub-sector performance and development of fodder innovation.